Cardiometabolic Risk Factors and Associated Features in 5th Grade Schoolchildren in Ouagadougou, Burkina Faso (West Africa) - Daboné, Charles; Delisle, Hélène; Receveur, Olivier (International Journal of Child Health and Nutrition, 2013)
The onset of cardiometabolic risk factors in childhood may be tracked into adulthood. However, little is known about such risk factors particularly in African schoolchildren. We conducted in Ouagadougou the capital city of Burkina Faso (West Africa) a cross-sectional study in 5th grade pupils of 12 schools (4 private and 8 public of which 2 were periurban). Weight, height, and blood pressure (BP) were measured and fasting serum lipids and glycaemia were determined. Sample mean age was 11.8±1.4 y (207 children, 51% girls). Mean total cholesterol (TC), LDL-C, HDL-C and triglycerides were 133.9, 83.5, 45.1 and 67.1 mg/dl, respectively; glycaemia stood at 87.9±7.1 mg/dl. Systolic (SBP) and Diastolic Blood Pressure (DBP) were 103.2 and 62.3 mmHg respectively. The main risk factor was low HDL-C (19.3%) followed by high TC and LDL-C (11.6% each). Elevated SBP and DBP were 9.7% and 4.3%, respectively. Being a girl was independently associated with increased serum lipids including HDL-C paradoxically. BMI was independently associated with increased BP. While attending a private school was independently associated (p<0.01) with higher HDL-C and lower TG and DBP, attending urban (vs periurban) school and higher age were independently associated with lower HDL-C. A sizeable proportion of children exhibited cardiometabolic risk factors and therefore, preventive measures would appear timely in low income country schoolchildren, and not only strategies targeting malnutrition